KELOR (Moringa oleifera Lam.): PEMANFAATAN DAN BIOAKTIVITAS - Endang Christine Purba (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2020)
Moringa oleifera Lam. (MO) is one of the plants that has been widely known its use by Indonesians which is calledKelor. MO belongs to Moringaceae family. Kelor is a useful plant that widely used as medicinal plants and ediblefood that it is called as an Amazing Tree dan The Miracle Tree. Moringa oleifera has several pharmacologicalpotentials, which are anti-microbial, antioxidant, nutritional food, anti-cancer and anti-diabetic. The writing ofthis article collects information on the use of ethnobotanical Moringa oleifera plants and the results of their testcontent. It is hoped that this information would become information to determine the other potential of Moringaoleifera as a source of both traditional and modern medicines. Keywords: amazing tree, moringa tea, anti-diabetic, malnutrition, anti-cancer